A polyacrylate polymer for resisting protein deposition and its preparation method and application
By copolymerizing specific zwitterionic structures with acrylate monomers, polyacrylate polymers that are resistant to protein deposition and calcification deposition are prepared, which solves the problem that hydrophilic materials are prone to deposition in artificial lenses and achieves improved anti-fouling performance and biocompatible effects.
Patent Information
- Application Number
- CN202410541089.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-30
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-04-30
AI Technical Summary
Hydrophilic polyacrylate materials tend to cause protein and cell deposition in intraocular lenses, resulting in reduced light transmittance and potential complications, and zwitterionic polymers are difficult to copolymerize with hydrophobic acrylate monomers under low moisture content conditions, resulting in Uneven polymerization.
By screening specific zwitterionic structures and copolymerizing with acrylate monomers, a polyacrylate polymer that is resistant to protein deposition and calcification deposition is prepared. The polymer is composed of 5% to 40% monomer A, 20% to 90% monomers Body B, 0% to 30% monomer C, 0.01% to 2% zwitterion, 0.05% to 2% free radical initiator and 1% to 20% crosslinking agent, the polymerization reaction conditions are 60~ 150℃, 12-72 hours.
This polymer effectively prevents or reduces the deposition of bacteria, proteins or cells on the surface of the intraocular lens device, reduces the probability of causing complications, and improves anti-fouling performance and biocompatibility, making it suitable for the preparation of intraocular lenses.
Smart Images

Figure CN118440240B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of intraocular lens polymer materials, and in particular to a polyacrylate polymer resistant to protein deposition and a preparation method and application thereof. Background Art
[0002] Generally, the eyes, corneas and lenses of healthy people have the ability to refract light, which can refract the light entering the eye and focus it on the retina to form a clear image. However, abnormal morphology of the eyeball or cornea or stiffness of the lens caused by aging may reduce the focusing ability of the eyeball, so that the cornea and lens cannot correctly focus the light on the retina and cannot form a clear image, which is refractive error. Correction of refractive error includes a variety of methods such as traditional frame glasses, contact lenses, laser eye surgery and lens implant surgery. Among them, laser eye surgery and lens implant surgery can not only correct the myopia, hyperopia and astigmatism of these patients, but also free patients from the trouble of wearing glasses every day. However, some patients cannot undergo laser eye surgery due to thin corneas, irregular corneal shapes or other corneal surgeries. Compared with laser eye surgery, lens implant surgery has the advantages of being able to correct extreme myopia, low requirements for preoperative pupil size, no restrictions on corneal thickness and shape, no damage to the cornea, smaller higher-order aberrations, better visual quality, and secondary removal. Therefore, lens implantation surgery is favored by more and more patients and is an important means of correcting refractive errors.
[0003] Implantable intraocular lenses such as intraocular lenses or phakic intraocular lenses are generally made of hydrophobic polyacrylate or hydrophilic polyacrylate materials, wherein intraocular lenses are mainly made of hydrophobic polyacrylate materials; phakic intraocular lenses are mainly made of hydrophilic polyacrylate materials; hydrophilic polyacrylate materials are soft, easy to fold and have good toughness, and are very suitable for implantation in the human eye, and will not cause damage to the human eye. Therefore, hydrophilic polyacrylate is currently one of the ideal materials for making intraocular lens devices. However, due to the high water content of hydrophilic polyacrylate, it is conducive to the flow exchange of cells and tissue fluids, resulting in bacteria, proteins or cells easily deposited on the surface of the intraocular lens device, causing a decrease in transmittance, affecting the performance of the lens device, and in more serious cases, it can also cause complications such as cataracts. This deficiency limits the application of hydrophilic polyacrylate materials in intraocular lenses. Therefore, how to reduce protein deposition and calcification without changing the transmittance, material properties and other bulk properties of hydrophilic polyacrylate materials needs to be solved urgently.
[0004] Zwitterionic polymers are a class of polymer materials that are electrically neutral as a whole and contain anionic and cationic groups on the side chains of some or all monomers, and have good biocompatibility. Its super hydrophilic property can form a tightly bound hydration layer on the surface of the material, thereby effectively preventing the adsorption of biological molecules such as proteins on the surface of the material. The existing application methods of zwitterionic polymers are mainly material surface modification and copolymerization. The surface modification method is to apply zwitterionic monomers or polymers to the surface of the material by dipping or spraying, and then combine the coating with the surface of the substrate material by heating, ultraviolet irradiation, microwave treatment and other methods. For example, the invention patent with publication number CN111790006A discloses a durable and stable hydrophilic antifouling coating for artificial lenses and its preparation method, which prevents the problem of protein and cell adhesion by applying the hydrophilic antifouling coating to the surface of the artificial lens, but the coating obtained in this way has a certain binding force, but it is easy to wear or fall off during long-term use, and the stability is insufficient.
[0005] The copolymerization method is to mix the zwitterionic compound monomer that can participate in the polymerization with the polymer raw material, and then obtain the polymerized material by heating initiation, light initiation and other methods. The zwitterionic polymer obtained in this way solves the problem of easy wear and shedding in the surface modification method. However, when the polyacrylate contains hydrophobic acrylate monomers, adding zwitterionic compounds to the monomer solution of acrylate polymer materials will cause phase separation, affecting the uniformity and stability of the material. Chinese invention patents with publication numbers CN109485785A and CN107118300A both report methods for obtaining soft contact lenses made of hydrogel or silicone hydrogel materials by copolymerizing zwitterionic compounds under hydrophilic conditions. However, both methods perform polymerization in a hydrophilic or aqueous solution of the polymerization raw materials as a whole. The hydrogel or silicone hydrogel materials have high softness and hydrophilicity, and a water content of 40-70%. Under this high water content, phase separation does not occur during the synthesis process, but the hardness is relatively low, and is not suitable for artificial lenses with more moderate hardness requirements, especially artificial lenses for phakic eyes. Since artificial lenses, especially phakic artificial lenses, contain both hydrophilic acrylate monomers and hydrophobic acrylate monomers in acrylic polymer materials, and the water content is generally lower than that of hydrogel or silicone hydrogel materials, which is about 20-40%. Therefore, when zwitterionic compounds are mixed with hydrophobic polymerizable monomers, phase separation will occur and the monomers cannot be completely miscible, resulting in the phenomenon of failure to polymerize or uneven polymerization. This characteristic limits the application of zwitterionic compounds in acrylate materials. It is urgent to develop an intraocular lens acrylate polymer that can simultaneously meet the requirements of lower water content for polymerization and have anti-protein deposition and calcification functions. Summary of the invention
[0006] The purpose of the present invention is to solve the above technical problems and provide a polyacrylate polymer that can simultaneously meet the requirements of low water content and has the functions of resisting protein deposition and calcification. Another purpose of the present invention is to provide the preparation of the polymer; another purpose of the present invention is to provide the use of the polymer in the preparation of an intraocular lens or a posterior chamber phakic intraocular lens; another purpose of the present invention is to provide an intraocular lens device that resists protein deposition and calcification deposition.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] A polyacrylate polymer capable of resisting protein deposition and calcification deposition is obtained by polymerization reaction of 5% to 40% by mass of monomer A, 20% to 90% by mass of monomer B, 0% to 30% by mass of monomer C, 0.01% to 2% by mass of zwitterion, 0.05% to 2% by mass of free radical initiator and 1% to 20% by mass of crosslinking agent as raw materials; the monomer A is at least one of acrylic acid, methacrylic acid, acrylate or methacrylate derivative; the monomer B is at least one of hydroxyalkyl acrylate or hydroxyalkyl methacrylate derivative monomer; and the monomer C is an ethylene derivative.
[0009] The present invention selects a specific zwitterionic structure that can be copolymerized with an acrylate monomer without phase separation, thereby solving the phase separation problem when a hydrophilic zwitterionic monomer is mixed with a hydrophobic acrylate monomer. The hydrophilic acrylate material obtained by polymerization is used to make an intraocular lens device, thereby improving the anti-fouling performance and biocompatibility, effectively preventing or reducing the deposition of bacteria, proteins or cells on the surface of the intraocular lens device, and thus reducing the probability of causing complications.
[0010] Furthermore, the acrylic acid ester in the monomer A is selected from alkyl acrylic acid ester or phenoxyalkyl acrylic acid ester; the methacrylic acid ester is selected from alkyl methacrylic acid ester or phenoxyalkyl methacrylic acid ester; the alkyl group is C 1-8 The phenoxyalkyl group is PhO(CH2) n -, n=1~8.
[0011] Furthermore, the alkyl group of the hydroxyalkyl acrylate or hydroxyalkyl methacrylate in the monomer B is C 1-8 A straight chain or branched chain alkyl group.
[0012] Furthermore, the ethylene derivative is selected from one or more of N-vinyl caprolactam, N-vinyl-2-pyrrolidone, N-vinyl-2-piperidone, and N-vinyl-2,5-pyrrolidinedione.
[0013] Further, the crosslinking agent is selected from one or more of 1,4-butanediol dimethacrylate, 1,3-propylene glycol dimethacrylate, ethylene glycol dimethacrylate, 1,4-butanediol diacrylate, 1,3-propylene glycol diacrylate, and ethylene glycol diacrylate.
[0014] Further, the zwitterion is: 2-(methacryloyloxy)ethyl-2-(trialkylamine)ethyl phosphate, wherein the alkyl group is C 1-8 A straight chain or branched alkyl group; or 2-(methacryloyloxy)ethyl-2-(dimethylarylamine)ethyl phosphate, wherein the aryl group is one or more of benzyl, 4-methylbenzyl, and 3-methylbenzyl.
[0015] Furthermore, the raw material of the polyacrylate polymer also includes 0.1% to 2% by mass of ultraviolet absorber and / or 0.1% to 2% by mass of blue light absorber. Adding ultraviolet absorber or blue light absorber to the artificial lens can prevent ultraviolet light or blue light from damaging the retina; for phakic artificial lenses, although natural lenses have a certain ability to absorb ultraviolet light or blue light, adding ultraviolet absorber or blue light absorber can still slow down the aging of natural lenses.
[0016] Furthermore, the blue light absorber is: 3-alkyl-1-aryl-4-[(4-vinylphenyl)diazenyl]-1H-pyrazole, wherein the alkyl group is a straight chain or branched chain alkyl group of C1-8, and the aryl group is one or more of phenyl, 4-methylphenyl, 3-methylphenyl, 1-naphthyl, and 2-naphthyl; or 3-alkyl-1,5-diaryl-4-[(4-vinylphenyl)diazenyl]-1H-pyrazole, wherein the alkyl group is a straight chain or branched chain alkyl group of C1-8, and the aryl group is one or more of phenyl, 4-methylphenyl, 3-methylphenyl, 1-naphthyl, and 2-naphthyl; the ultraviolet absorber is an ultraviolet absorber containing a benzophenone or benzotriazole group.
[0017] Preferably, the ultraviolet absorber is selected from one or more of 2-[3-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]ethyl 2-methylacrylate and 2-(4-benzoyl-3-hydroxyphenoxy)ethyl 2-acrylate.
[0018] Furthermore, the free radical initiator is: azocyclohexane, azobisisobutyronitrile, benzoyl peroxide, or tert-butyl peroxyalkyl carbonate, wherein the alkyl group in the tert-butyl peroxyalkyl carbonate is C 1-10 A straight chain or branched chain alkyl group.
[0019] The present invention also provides the above polyacrylate polymer prepared by the following method:
[0020] S1. The various monomers A, B, C, crosslinking agents, zwitterions and free radical initiators in the raw materials are prepared into a uniform mixture;
[0021] S2. Remove air from the mixed solution, and polymerize the mixed solution at a temperature of 60 to 150° C. for 12 to 72 hours under an inert atmosphere to obtain a polyacrylate polymer.
[0022] Since the above-mentioned polyacrylate polymer can solve the phase separation problem when the hydrophilic zwitterionic monomer and the hydrophobic acrylate monomer are mixed, and can improve the anti-fouling performance and biocompatibility, it can effectively prevent or reduce the deposition of bacteria, proteins or cells on the surface of the intraocular lens device, thereby reducing the probability of causing complications.
[0023] Therefore, the present invention claims the use of the above-mentioned polyacrylate polymer in the preparation of intraocular lens devices.
[0024] The present invention provides an intraocular lens device resistant to protein deposition and calcification deposition, wherein at least the optical main body of the intraocular lens device is composed of the above-mentioned polyacrylate polymer.
[0025] Furthermore, the intraocular lens device is an intraocular lens or a posterior chamber phakic intraocular lens.
[0026] The present invention also provides a blue light filtering intraocular lens device that resists protein deposition and calcification deposition, wherein the blue light filtering intraocular lens device is a blue light filtering posterior chamber phakic intraocular lens; at least the optical main body of the blue light filtering posterior chamber phakic intraocular lens comprises the above-mentioned polyacrylate polymer.
[0027] The preparation method of the above-mentioned anti-protein deposition and anti-calcification deposition blue light filtering intraocular lens device is as follows: the mixed solution obtained according to the above-mentioned polyacrylate polymer preparation method S1 is placed in the mold required for the blue light filtering intraocular lens device, and the blue light filtering intraocular lens device containing the anti-protein deposition and anti-calcification deposition polymer is prepared according to step S2.
[0028] The beneficial effects of the present invention are as follows:
[0029] (1) The present invention solves the phase separation problem when a hydrophilic zwitterionic monomer and a hydrophobic acrylate monomer are mixed by modifying the structure of the zwitterionic monomer and copolymerizing it with an acrylate monomer. The hydrophilic acrylate material obtained by polymerization is used to make an intraocular lens device, which improves the anti-fouling performance and biocompatibility, effectively prevents or reduces the deposition of bacteria, proteins or cells on the surface of the intraocular lens device, and thus reduces the probability of causing complications.
[0030] (2) The glass transition temperature of the acrylic ester polymer of the present invention is 80°C or higher, the short-wave blue light transmittance of 400-470nm is not higher than 85%, and the visible light transmittance greater than 550nm is higher than 90%; after the acrylic ester polymer is fully hydrated in purified water, its equilibrium water content is 20%-40%, which can meet the material requirements of artificial lenses.
[0031] (3) At the same time, the intraocular lens device adds a blue light absorber to the hydrophilic acrylate material for copolymerization. The intraocular lens device can effectively filter short-wavelength blue light to reduce the damage of blue light to the retina without affecting normal vision. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The intraocular lenses with an optical power of -15D prepared from the materials of Example 1(a), Example 9(b) and Example 10(c) were implanted under the skin of a rabbit for 3 months and then removed. The images are taken under an optical microscope.
[0033] Figure 2 The intraocular lenses with an optical power of -15D prepared from the materials of Comparative Examples 5(d), 7(e), 8(f) and 10(g) were implanted subcutaneously in rabbits for 3 months and then removed. The images are taken under an optical microscope. DETAILED DESCRIPTION
[0034] In order to make the technical personnel in the technical field better understand the scheme of the present invention, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention. Obviously, the described embodiment is only an embodiment of a part of the present invention, rather than all embodiments. The reagents or materials in the embodiment of the present invention are all commercially available unless otherwise specified, and are reagents or materials that the public can obtain by purchasing; based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the art without making creative work should belong to the scope of protection of the present invention.
[0035] Example 1
[0036] A polyacrylate polymer for resisting protein deposition and calcification deposition, wherein the polyacrylate polymer is composed of the components and contents shown in Table 1, and the preparation method thereof is as follows:
[0037] S1. The various monomers A, B, C, crosslinking agents, zwitterions, blue light absorbers, UV absorbers and free radical initiators in the raw materials shown in Table 1 are prepared into a uniform mixture;
[0038] S2. removing air from the mixed solution, and polymerizing the mixed solution by heating under an inert atmosphere to obtain a polyacrylate polymer.
[0039] Table 1 Raw material composition of polyacrylate polymer of Example 1.
[0040]
[0041] The specific preparation method is as follows:
[0042] In a three-necked round-bottom glass flask, 200 g of hydroxyethyl acrylate, 60 g of ethyl methacrylate, 40 g of methacrylic acid, 80 g of N-vinyl-2,5-pyrrolidinedione, 8 g of ethylene glycol diacrylate, 2 g of 2-[3-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate, 2 g of 3-methyl-1-phenyl-4-[(4-vinylphenyl)diazenyl]-1H-pyrazole, 4 g of 2-(methacryloyloxy)ethyl-2-(triethylamine)ethyl phosphate and 4 g of azobisisobutyronitrile were added as shown in Table 1, and the mixture was stirred under a nitrogen atmosphere until the mixed solution became a transparent liquid, and stirring was continued for 60 min.
[0043] Under nitrogen protection, the mixed liquid is transferred to a sheet mold and placed in a constant temperature oven, and the polymerization conditions are set at 60°C for 4 hours, 90°C for 2 hours, and 110°C for 24 hours to obtain a polyacrylate polymer. The polyacrylate polymer is made into a sheet material, and then cut into a round rough wafer, which is mechanically cut into a butterfly wafer with an optical surface, and the butterfly wafer is carved to prepare the desired intraocular lens.
[0044] Example 2
[0045] A polyacrylate polymer for resisting protein deposition and calcification deposition, wherein the polyacrylate polymer is composed of the components and contents shown in Table 2, and the preparation method thereof is as follows:
[0046] S1. The various monomers A, B, C, crosslinking agents, zwitterionic blue light absorbers, UV absorbers and free radical initiators in the raw materials shown in Table 2 are prepared into a uniform mixture;
[0047] S2. removing air from the mixed solution, and polymerizing the mixed solution by heating under an inert atmosphere to obtain a polyacrylate polymer.
[0048] Table 2 Raw material composition of polyacrylate polymer of Example 2.
[0049]
[0050] The specific preparation method is as follows: referring to the method of Example 1, the raw materials in Table 2 are mixed, stirred under a nitrogen atmosphere until the mixed solution becomes a transparent liquid, and stirred for 60 minutes. Under the protection of nitrogen, the mixed liquid is transferred to a sheet mold, and placed in a constant temperature oven, and the polymerization conditions are set to 60° C. for 3 hours, 90° C. for 6 hours, and 110° C. for 24 hours, so as to obtain a polyacrylate polymer. The polyacrylate polymer is made into a sheet material, and then cut into a round rough wafer, mechanically cut into a butterfly wafer with an optical surface, and the butterfly wafer is carved to prepare the desired intraocular lens.
[0051] Example 3
[0052] A polyacrylate polymer for resisting protein deposition and calcification deposition, wherein the polyacrylate polymer is composed of the components and contents shown in Table 3, and the preparation method thereof is as follows:
[0053] S1. The various monomers A, B, C, crosslinking agents, zwitterionic blue light absorbers, UV absorbers and free radical initiators in the raw materials shown in Table 3 are prepared into a uniform mixture;
[0054] S2. removing air from the mixed solution, and polymerizing the mixed solution by heating under an inert atmosphere to obtain a polyacrylate polymer.
[0055] Table 3 Raw material composition of polyacrylate polymer of Example 3.
[0056]
[0057] The specific preparation method is as follows: Mix the raw materials in Table 3 according to the method of Example 1, stir under nitrogen atmosphere until the mixed solution becomes a transparent liquid, continue stirring for 60 minutes, transfer the mixed liquid to a sheet mold under nitrogen protection, and put it into a constant temperature oven, set the polymerization conditions to 70°C for 8 hours, 100°C for 10 hours, and 120°C for 16 hours, and obtain a polyacrylate polymer. The polyacrylate polymer is made into a sheet material, and then cut into a round rough wafer, mechanically cut to prepare a butterfly wafer with an optical surface, and the butterfly wafer is carved to prepare the desired intraocular lens.
[0058] Example 4
[0059] A polyacrylate polymer for resisting protein deposition and calcification deposition, wherein the polyacrylate polymer is composed of the components and contents shown in Table 4, and the preparation method thereof is as follows:
[0060] S1. The various monomers A, B, C, crosslinking agents, zwitterionic blue light absorbers, UV absorbers and free radical initiators in the raw materials shown in Table 4 are prepared into a uniform mixture;
[0061] S2. removing air from the mixed solution, and polymerizing the mixed solution by heating under an inert atmosphere to obtain a polyacrylate polymer.
[0062] Table 4 Raw material composition of polyacrylate polymer of Example 4.
[0063]
[0064] The specific preparation method is as follows: referring to the method of Example 1, the raw materials in Table 4 are mixed, stirred under a nitrogen atmosphere until the mixed solution becomes a transparent liquid, and the stirring is continued for 120 minutes. Under the protection of nitrogen, the mixed liquid is transferred to a sheet mold, and placed in a constant temperature oven, and the polymerization conditions are set to 50° C. for 6 hours, 80° C. for 6 hours, and 100° C. for 18 hours, so as to obtain a polyacrylate polymer. The polyacrylate polymer is made into a sheet material, and then cut into a round rough wafer, mechanically cut into a butterfly wafer with an optical surface, and the butterfly wafer is carved to prepare the desired intraocular lens.
[0065] Example 5
[0066] A polyacrylate polymer for resisting protein deposition and calcification deposition, wherein the polyacrylate polymer is composed of the components and contents shown in Table 5, and the preparation method thereof is as follows:
[0067] S1. The various monomers A, B, C, crosslinking agents, zwitterionic blue light absorbers, UV absorbers and free radical initiators in the raw materials shown in Table 5 are prepared into a uniform mixture;
[0068] S2. removing air from the mixed solution, and polymerizing the mixed solution by heating under an inert atmosphere to obtain a polyacrylate polymer.
[0069] Table 5 Raw material composition of polyacrylate polymer of Example 5.
[0070]
[0071] The specific preparation method is as follows: referring to the method of Example 1, the raw materials in Table 5 are mixed, stirred under a nitrogen atmosphere until the mixed solution becomes a transparent liquid, and stirred for 60 minutes. Under the protection of nitrogen, the mixed liquid is transferred to a sheet mold, and placed in a constant temperature oven, and the polymerization conditions are set to 60° C. for 3 hours, 90° C. for 6 hours, and 110° C. for 24 hours, so as to obtain a polyacrylate polymer. The polyacrylate polymer is made into a sheet material, and then cut into a round rough wafer, mechanically cut into a butterfly wafer with an optical surface, and the butterfly wafer is carved to prepare the desired intraocular lens.
[0072] Example 6
[0073] A polyacrylate polymer for resisting protein deposition and calcification deposition, wherein the polyacrylate polymer is composed of the components and contents shown in Table 6, and the preparation method thereof is as follows:
[0074] S1. The various monomers A, B, C, crosslinking agents, zwitterionic blue light absorbers, UV absorbers and free radical initiators in the raw materials shown in Table 6 are prepared into a uniform mixture;
[0075] S2. removing air from the mixed solution, and polymerizing the mixed solution by heating under an inert atmosphere to obtain a polyacrylate polymer.
[0076] Table 6 Raw material composition of polyacrylate polymer of Example 6.
[0077]
[0078] The specific preparation method is as follows: Mix the raw materials in Table 6 according to the method of Example 1, stir under nitrogen atmosphere until the mixed solution becomes a transparent liquid, continue stirring for 30 minutes, transfer the mixed liquid to a sheet mold under nitrogen protection, and put it into a constant temperature oven, set the polymerization conditions to 60°C for 10 hours, 90°C for 6 hours, and 110°C for 48 hours, and obtain a polyacrylate polymer. The polyacrylate polymer is made into a sheet material, and then cut into a round rough wafer, mechanically cut into a butterfly wafer with an optical surface, and the butterfly wafer is carved to prepare the desired intraocular lens.
[0079] Example 7
[0080] The preparation method is the same as that of Example 1, except that the components do not contain a blue light absorber to prepare an artificial lens.
[0081] Example 8
[0082] The preparation method is the same as that of Example 1, except that the components do not contain ultraviolet absorbers to prepare an artificial lens.
[0083] Comparative Examples 1-2
[0084] The preparation method is the same as that of Example 1, except that the content of monomer A is increased to 50% (30% ethyl methacrylate, 20% methacrylic acid) and the content of monomer A is reduced to 0% to prepare an artificial lens.
[0085] Comparative Examples 3-4
[0086] The preparation method is the same as that of Example 1, except that the content of the component monomer B is changed to 95% and 10% respectively, and the artificial lenses of Comparative Example 3 and Comparative Example 4 are prepared.
[0087] Comparative Examples 5-6
[0088] The preparation method is the same as that of Example 1, except that the content of zwitterions is changed to 0.001% and 5% respectively, to prepare comparative example 5 and comparative example 6 intraocular lenses.
[0089] Embodiments 9-10
[0090] The preparation method is the same as that of Example 1, except that the types of zwitterions are changed to the same type of 2-(methacryloyloxy)ethyl-2-(trimethylamine)ethyl phosphate and 2-(methacryloyloxy)ethyl-2-(tri-n-butylamine)ethyl phosphate, respectively, to prepare the artificial lenses of Example 9 and Example 10.
[0091] Comparative Examples 7 to 8
[0092] The preparation method is the same as that of Example 1, except that the types of component zwitterions are changed to different types of zwitterions 3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate and 2-methacryloyloxyethyl sulfobetaine, respectively, to prepare the comparative examples 7 and 8 intraocular lenses.
[0093] Comparative Example 9
[0094] The preparation method is the same as that of Example 1, except that the monomer B is absent, and the artificial lens of Comparative Example 9 is prepared.
[0095] Comparative Example 10
[0096] The preparation method is the same as that of Example 1, except that there is no zwitterion, and the prepared intraocular lens is Comparative Example 10.
[0097] Experimental Example 1 Spectral transmittance test
[0098] 1. Experimental Methods
[0099] The transmittance of the intraocular lens with a focal power of -15D prepared in Examples 1 to 10 in the 395nm, 450nm, 500nm and 550nm bands was tested using a UV-visible spectrometer to characterize the optical properties of the material. For lenses with the same focal power, a higher material refractive index can make the optical zone thinner. The test method steps adopted refer to method 4.4 in YY 0290.2-2021 "Ophthalmic Optical Intraocular Lenses Part II: Optical Properties and Test Methods".
[0100] 2. Experimental results
[0101] The experimental results are shown in Table 7. It can be seen from Table 7 that the materials obtained in Examples 1 to 6 all have the function of absorbing ultraviolet light and filtering blue light. Example 7 does not add a blue light absorber, and the material obtained has a 450nm transmittance greater than 90%, and has no blue light filtering function. Example 8 does not add an ultraviolet absorber, and the material obtained has a 395nm transmittance greater than 10%, and has no ultraviolet absorption function. Examples 9 and 10 change the type of component zwitterions to the same type of zwitterions, and the effects are similar to those of Examples 1 to 6.
[0102] Table 7: Test of intraocular lens transmittance in Examples 1 to 10
[0103] sample 395nm transmittance 450nm transmittance 500nm transmittance 550nm transmittance Example 1 10% 60% 90% 95% Example 2 10% 65% 90% 95% Example 3 10% 70% 90% 95% Example 4 20% 70% 90% 95% Example 5 15% 65% 90% 95% Example 6 10% 60% 90% 95% Example 7 15% 90% 90% 95% Example 8 40% 65% 90% 95% Example 9 10% 60% 90% 95% Example 10 10% 60% 90% 95%
[0104] Experimental Example 2: Material Refractive Index and Uniformity Measurement
[0105] It is difficult to directly judge whether phase separation will occur during the material synthesis process and the uniformity of the prepared material. Therefore, this patent characterizes the uniformity of the material by measuring the refractive index of different parts of the prepared sheet material and measuring the image quality of the prepared artificial lens. The sampling method for different parts is the three-point sampling method, that is, 17mm to 20mm discs are cut at the center, upper left corner and lower right corner of the material, and then further processed into a suitable measurement size and thickness for refractive index characterization.
[0106] 1. Experimental Methods
[0107] The refractive index of the round rough wafers prepared in Examples 1 to 8 and Comparative Examples 1 to 10 was tested using an Abbe refractometer, and three groups were tested in parallel to characterize the uniformity of the material. The surface of the test sample in contact with the reference plane of the refractometer was polished to a smooth finish and immersed in a physiological saline solution at 20°C ± 0.5°C for at least 12 hours; the excess water on the sample surface was gently sucked or shaken off and then measured immediately.
[0108] The modulation transfer function (MTF) value of the artificial lens with a focal power of -15D prepared in Examples 1 to 8 and Comparative Examples 1 to 10 under a 3mm aperture diaphragm was tested using an artificial lens automatic focus meter to characterize the image quality of the artificial lens prepared from the material. The test method steps adopted refer to method 4.3 in YY0290.2-2021 "Ophthalmic Optics Intraocular Lenses Part II: Optical Properties and Test Methods".
[0109] 2. Experimental results
[0110] The experimental results are shown in Table 8. It can be seen from Table 8 that the refractive index of the three groups of circular rough crystals prepared in Examples 1 to 8 in parallel tests is the same, and the image quality of the prepared artificial lenses meets the industry standard requirements (MTF is greater than 70% of the theoretical maximum achievable value), which shows that the materials prepared by these methods have good uniformity.
[0111] The refractive index of the three groups of circular rough wafers prepared in comparative examples 1 to 5 and 9 to 10 tested in parallel was the same, and the uniformity under this test was also good. The refractive index of the three groups of circular rough wafers prepared in comparative examples 6 to 8 tested in parallel was different, and the image quality of the prepared artificial lenses was very poor, which indicates that the materials prepared by these methods are not uniform.
[0112] Table 8 Refractive index and MTF of Examples 1 to 8
[0113]
[0114] Experimental Example 3 Hardness and Water Content Determination
[0115] 1. Experimental Methods
[0116] The compression force of the intraocular lenses with an optical power of -15D prepared in Examples 1 to 10 and Comparative Examples 1 to 4 and 9 at the compression diameter of 11 mm of the support part is used to characterize the hardness of the material. The test method steps adopted refer to the method 4.4 in YY0290.3-2018 "Ophthalmic Optical Intraocular Lenses Part III: Mechanical Properties and Test Methods".
[0117] The water content of the intraocular lenses with a focal power of -15D prepared in Examples 1 to 10 and Comparative Examples 1 to 4 and 9 was tested to characterize the water permeability of the material. The test method adopted was the weighing method, and the dry weight and water weight of the sample were measured at room temperature, and the water content was calculated according to formula (1):
[0118]
[0119] Where:
[0120] m 含水 ——The mass of the test sample in its equilibrium water state
[0121] m 干态 ——Test sample dry quality
[0122] The method for determining the mass of the equilibrium water content is as follows: immerse the sample in a purified water solution at 20℃±0.5℃ for at least 12 hours. Use a dry, dust-free cloth to gently absorb excess water from the sample surface and then weigh it using an analytical balance.
[0123] The dry mass determination method is as follows: dry the sample in equilibrium water-containing state in an oven at 100°C ± 10°C to a constant mass (generally 16h to 18h), seal it in a sealed container with an active desiccant, cool it to room temperature, and weigh it using an analytical balance.
[0124] 2. Experimental results
[0125] The experimental results are shown in Table 9. It can be seen from Table 9 that the compression force of Examples 1 to 10 is between 36 mg and 40 mg, and the water content is between 36 and 38%. Compared with the control example, the compression force and the water content are both too large or too small. It can be seen that the artificial lens prepared in the embodiments of the present invention can achieve a good level in terms of hardness and water content, and is suitable for the requirements of artificial lens materials.
[0126] Table 9 Water content and compression force test of artificial lens of Examples 1 to 10 and Comparative Examples 1 to 4 and 9
[0127]
[0128]
[0129] Experimental Example 4 Protein and Calcification Deposition Determination
[0130] 1. Experimental Methods
[0131] The artificial lenses with an optical power of -15D prepared in Examples 1, 9, 10 and Comparative Examples 5, 7, 8, and 10 were used for rabbit subcutaneous lens implantation surgery experiments to characterize the material's anti-protein and calcification deposition performance. When impurities appear on the surface of the lens, they appear as black attachments under a microscope, indicating protein deposition and calcification. The test method steps adopted refer to Method 6.5 in YY0290.5-2023 "Ophthalmic Optical Intraocular Lenses Part V: Biocompatibility", and all lenses were removed 3 months after implantation.
[0132] 2. Experimental results
[0133] The experimental results are as shown in the attached manual. Figure 1 and Figure 2 As shown, there is no protein deposition and calcification deposition on the crystal surface of Example 1, indicating that the material has high resistance to protein deposition and calcification deposition. There is no protein deposition on the crystal surface of Examples 9 and 10, indicating that the same type of zwitterions have high resistance to protein deposition and calcification deposition. There are many proteins and calcification deposition on the crystal surface of Comparative Example 5 ( Figure 2 The black part in the middle shows that the content of zwitterions in the components is changed, and the material's ability to resist protein deposition and calcification deposition is reduced. The black adhering crops on the crystal surfaces of Comparative Examples 7 and 8, namely, protein deposition, are more, and significant calcification occurs, indicating that the addition of other types of zwitterions results in poor material uniformity, and the ability to resist protein deposition and calcification deposition is reduced. The crystal surface of Comparative Example 10 has more protein deposition and obvious calcification, indicating that without the addition of zwitterions, the material's ability to resist protein deposition and calcification deposition is reduced.
[0134] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the solution. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents based on the understanding of the present solution without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A polyacrylate polymer that resists protein deposition and calcification deposition, characterized in that: The acrylate polymer is obtained by polymerization reaction of 5% to 40% by weight of monomer A, 20% to 90% by weight of monomer B, 1% to 30% by weight of monomer C, 0.01% to 2% by weight of zwitterion, 0.05% to 2% by weight of free radical initiator and 1% to 20% by weight of crosslinking agent as raw materials; the monomer A is at least one of acrylic acid, methacrylic acid, acrylate or methacrylate; the monomer B is at least one of hydroxyalkyl acrylate or hydroxyalkyl methacrylate monomer; the monomer C is an ethylene derivative; The monomer C ethylene derivative is selected from N - Vinyl caprolactam, N -vinyl-2-pyrrolidone, N -vinyl-2-piperidone, N - one or more of vinyl-2,5-pyrrolidinedione; The zwitterion is: 2-(methacryloyloxy)ethyl-2-(trialkylamine)ethyl phosphate, wherein the alkyl group is C 1-8 A straight or branched alkyl group; or 2-(methacryloyloxy)ethyl-2-(dimethylarylamine)ethyl phosphate, wherein the aryl group is one or more of benzyl, 4-methylbenzyl, and 3-methylbenzyl; After the acrylic ester polymer is hydrated, its water content is 20% to 40%.
2. The polyacrylate polymer according to claim 1, characterized in that The acrylic acid ester in the monomer A is selected from alkyl acrylic acid ester or phenoxyalkyl acrylic acid ester; the methacrylic acid ester is selected from alkyl methacrylic acid ester or phenoxyalkyl methacrylic acid ester; the alkyl group is C 1-8 The phenoxyalkyl group is PhO(CH2) n -, n=1~8.
3. The polyacrylate polymer according to claim 1, characterized in that The alkyl group of the hydroxyalkyl acrylate or hydroxyalkyl methacrylate in the monomer B is C 1-8 A straight chain or branched chain alkyl group.
4. The polyacrylate polymer according to claim 1, characterized in that The crosslinking agent is selected from one or more of 1,4-butanediol dimethacrylate, 1,3-propylene glycol dimethacrylate, ethylene glycol dimethacrylate, 1,4-butanediol diacrylate, 1,3-propylene glycol diacrylate, and ethylene glycol diacrylate.
5. The polyacrylate polymer according to claim 1, characterized in that The raw materials of the polyacrylate polymer also include 0.1% to 2% by mass of an ultraviolet absorber and / or 0.1% to 2% by mass of a blue light absorber.
6. The polyacrylate polymer according to claim 5, characterized in that The blue light absorber is: 3-alkyl-1-aryl-4-[(4-vinylphenyl)diazenyl]-1H-pyrazole, wherein the alkyl group is C 1-8 wherein the alkyl group is a straight chain or branched alkyl group, the aryl group is one or more of phenyl, 4-methylphenyl, 3-methylphenyl, 1-naphthyl, and 2-naphthyl; or 3-alkyl-1,5-diaryl-4-[(4-vinylphenyl)diazenyl]-1H-pyrazole, wherein the alkyl group is C 1-8 The straight chain or branched alkyl group is selected from the group consisting of phenyl, 4-methylphenyl, 3-methylphenyl, 1-naphthyl and 2-naphthyl. The ultraviolet absorber is an ultraviolet absorber containing a benzophenone or benzotriazole group.
7. The polyacrylate polymer according to claim 5, characterized in that The ultraviolet absorber is selected from 2-[3-(2 H -benzotriazol-2-yl)-4-hydroxyphenyl]ethyl-2-methylacrylate, 2-acrylate-2-(4-benzoyl-3-hydroxyphenoxy)ethyl ester or one or more thereof.
8. The polyacrylate polymer according to claim 1, characterized in that The free radical initiator is: azocyclohexane, azobisisobutyronitrile, benzoyl peroxide, or tert-butyl peroxyalkyl carbonate, wherein the alkyl group in the tert-butyl peroxyalkyl carbonate is C 1-10 A straight chain or branched chain alkyl group.
9. The polyacrylate polymer according to claim 1, characterized in that The polyacrylate polymer is prepared by the following method: S1. The various monomers A, B, C, crosslinking agents, zwitterions and free radical initiators in the raw materials are prepared into a uniform mixture; S2. Remove air from the mixed solution, and polymerize the mixed solution at a temperature of 60 to 150° C. for 12 to 72 hours under an inert atmosphere to obtain a polyacrylate polymer.
10. Use of the polyacrylate polymer according to claim 1 in preparing an intraocular lens device.
11. The use according to claim 10, characterized in that: The intraocular lens device is an artificial lens.
12. The use according to claim 10, characterized in that: The intraocular lens device is a posterior chamber phakic intraocular lens.
13. An intraocular lens device resistant to protein deposition and calcification deposition, characterized in that: At least the optical body portion of the intraocular lens device is composed of the polyacrylate polymer according to any one of claims 1-8.
14. The intraocular lens device according to claim 13, wherein: The intraocular lens device is an artificial lens.
15. The intraocular lens device according to claim 13, wherein: The intraocular lens device is a posterior chamber phakic intraocular lens.
16. A blue light filtering intraocular lens device that resists protein deposition and calcification deposition, characterized in that: The blue light filtering intraocular lens device is a blue light filtering posterior chamber phakic intraocular lens; at least the optical main body of the blue light filtering posterior chamber phakic intraocular lens comprises the polyacrylate polymer of claim 5 or 6.
Citation Information
Patent Citations
Hydrogel soft contact lens material containing betaine zwitter-ion and preparation method of hydrogel soft contact lens material
CN107118300A
Silicone hydrogel composition, ophthalmic lens and preparation method of ophthalmic lens
CN109485785A
Durable and stable hydrophilic dirt-resisting coating for intraocular lens and preparation method of durable and stable hydrophilic dirt-resisting coating
CN111790006A
Photoinduced hyperchromic yellow intraocular lens device and preparation method thereof
CN103705973A
Hydrogel contact lens having high water content and inhibiting protein adsorption and method for preparing the same
KR1020180001201A